Cohort profile: design and first results of the Dutch IBD Biobank: a prospective, nationwide biobank of patients with inflammatory bowel disease. Issue 11 (8th November 2017) - Spekhorst, Lieke M; Imhann, Floris; Festen, Eleonora AM; Bodegraven, Ad A van; Boer, Nanne KH de; Bouma, Gerd; Fidder, Herma H; D'Haens, Geert; Hoentjen, Frank; Hommes, Daan W; Jong, Dirk J de; Löwenberg, Mark; et al.
Abstract : Purpose: The Dutch IBD Biobank aims to facilitate the discovery of predictors for individual disease course and treatment response in patients with inflammatory bowel disease (IBD). In this paper, we aim to describe the establishment of the Dutch IBD Biobank, including the facilitators and barriers to establishment. Moreover, we aim to provide a complete overview of the content of the Dutch IBD Biobank. Participants: Since 2007, every patient with IBD treated in one of the eight Dutch university medical centres is asked to participate in the Dutch IBD Biobank in which 225 standardised IBD-related data items and biomaterials, such as serum, DNA, biopsies and a stool sample, are collected. Findings to date: As of June 2014, the Dutch IBD Biobank had enrolled 3388 patients with IBD: 2118 Crohn's disease (62.5%), 1190 ulcerative colitis (35.1%), 74 IBD-unclassified (2.2%) and 6 IBD-indeterminate (0.2%). The inclusion of patients with IBD is ongoing. The quality of the biomaterials is good and serum, DNA and biopsies have been used in newly published studies. Future plans: The genotyping (750 000 genetic variants) of all participants of the Dutch IBD Biobank is currently ongoing, enabling more genetic research. In addition, all participants will start reporting disease activity and outcome measures using an online platform and mobile app .